Controllable synthesis of Mn3O4 nanodots@nitrogen-doped graphene and its application for high energy density supercapacitors. Issue 11 (28th February 2017) - Liu, Li; Su, Lijun; Lang, Junwei; Hu, Bin; Xu, Shan; Yan, Xingbin
Abstract : Supercapacitors using ionic liquids (ILs) as electrolytes have triggered great interest due to their much higher energy density when compared to aqueous supercapacitors. Abstract : Supercapacitors using ionic liquids (ILs) as electrolytes have triggered great interest due to their much higher energy density when compared to aqueous supercapacitors. Although manganese oxides have obvious capacitive contribution in ILs and thus can be used as electrode materials for IL-based supercapacitors, they suffer from low specific capacitance in ILs. Here Mn3 O4 nanodots loaded on nitrogen-doped graphene sheets (denoted as Mn3 O4 NDs@NG) are prepared through a facile one-pot solvothermal method with the presence of octylamine as the surfactant. Octylamine plays an important role in obtaining quantum-sized Mn3 O4 NDs and controlling their dispersion degree on the surface of NG. With an optimal loading mass of Mn3 O4 NDs, the corresponding Mn3 O4 NDs@NG material is able to achieve a high specific capacitance of 158.9 F g −1 in a given IL and shows excellent rate capability. On this basis, a symmetric supercapacitor is assembled based on such a Mn3 O4 NDs@NG, which delivers a high energy density of 90.7 W h kg −1 in the IL electrolyte. Furthermore, an asymmetric supercapacitor is also built by using such a Mn3 O4 NDs@NG and activated carbon as the negative and positive electrode, respectively. This asymmetric device shows a higher energy density of 124.4 W h kg −1 compared to the symmetric one, and it still can deliver 55.8 W h kg −1 at a large power density of 29.9 kW kg −1 .